SEMINAR PEMBERIAN CODMAN PENDULAR EXERCISE TERHADAP PENINGKATAN LINGKUP GERAK SENDI PENDERITA FROZEN SHOULDER DI RUMAH SAKIT GRANDMED LUBUK PAKAM - Siti Sarah Bintang Sarah Bintang; Sabirin Berampu; Mawaddah Saleha; Miftahul Zannah; Simson Sinuhaji; Leni Sumiati Silaban (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
Frozen shoulder or another name for adhesive capsulitis is pain that results in limited Range of Motion (ROM). Frozen shoulder or another name for adhesive capsulitis is pain that results in limited Range of Motion (ROM). Codman pendular exercises are interventions or techniques often used by physiotherapists to increase Range of Motion (ROM). This service activity is carried out through seminars using lecture, question and answer methods and demonstrations. The samples taken were patients with frozen shoulder with a total of 14 people. The statistical test results obtained p-value <0.05, it can be concluded that the hypothesis in the study was accepted, namely: